Leadership in Action: Dividends and Interest - News Flash: 360-Degree Feedback is Alive and Well - Chappelow, Craig (Center for Creative Leadership, 2003)
A great deal of a 360-degree-feedback program's success depends on responsible planning, use, and follow-up.